OFDI and foreign trade: evidence from developing countries - Li, Jingwen; Soh, Wei Ni; Mohd Ashhari, Zariyawati; Kamarudin, Fakarudin (Better Advances Press, 2023)
In this paper, we select a panel data of 64 developing and developed countries from 2010-2019 as our research sample and we use four estimation methods, pooled OLS, fixed effects estimation, random effects estimation and systematic GMM estimation models with static and dynamic panel data to explore the impact of foreign trade on OFDI. The results of the study show that export trade volume, import trade volume and openness all have a positive impact on OFDI. This is in line with the hypothesis of the study. As for the control variables, economic development level, labour force and urbanization percentage all have a positive effect on OFDI. Country dummy variables are included in this paper to differentiate between developing and developed countries. The dummy variables are not significant, which may be due to the strong effect of foreign trade, resulting in insignificant dummy variables.